\(a^3+b^3+c^3=3abc\)
\(\Leftrightarrow\left(a+b+c\right)\left(a^2+b^2+c^2-ab-bc-ac\right)=0\)
\(\Leftrightarrow a^2+b^2+c^2-ab-bc-ac=0\) (vì \(a+b+c\ne0\))
<=> \(2a^2+2b^2+2c^2-2ab-2bc-2ac=0\) (nhân cả hai về với hai)
<=> \(\left(a^2-2ab+b^2\right)+\left(b^2-2bc+c^2\right)+\left(c^2-2ac+a^2\right)=0\)
<=> \(\left(a-b\right)^2+\left(b-c\right)^2+\left(c-a\right)^2=0\)
<=> a - b = b - c = c - a = 0 (vì 3 cái đấy đều lớn hơn hoặc bằng 0)
<=> a = b = c
Nên : P = \(\left(2017+\frac{a}{b}\right)\left(2017+\frac{b}{c}\right)\left(2017+\frac{c}{a}\right)=\left(2017+\frac{a}{a}\right)\left(2017+\frac{a}{a}\right)+\left(2017+\frac{a}{a}\right)\)
\(=\left(2017+1\right)\left(2017+1\right)\left(2017+1\right)=2018.2018.2018=2018^3\)